Tunable-spacing multi-wavelength yb-doped fiber laser (YDFL) based on temperature sensitive loop mirror - Lim, Kok Sing; Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Ahmad, Harith (Old City Publishing, 2010)
A tunable quad-wavelength Yb-doped fiber laser is demonstrated using a novel temperature-sensitive loop mirror. The loop mirror consists of two segments of polarization maintaining fibres which are spliced at an offset rotation angle of 90°. From this a quad-wavelength lasing with a constant spacing of around 1.74 nm, a flat output power of -12 dBm, a signal to noise ratio of more than 32 dB was obtained in the 1037 nm wavelength region. The wavelength spacing and tuning span could be easily tuned by manipulating the polarizing maintaining fibre (PMF) length parameters and temperature of the loop mirror. The wavelength spacing and tuning span of the laser was larger if longer PMF segments were used in the loop mirror.